ANALYSIS OF TOURISM PRODUCT MARKETING STRATEGY IN PT. ALMIN AHSAN TRAVEL - Qonitah, Aisha; Nugraha, D.K.S (Journal of Indonesian Tourism and Policy Studies, 2021)
This study discusses the marketing strategy of tourism products that happened at PT. Experience Ahsan Travel. Nowadays, the development of Umrah Hajj travel in Indonesia is increasing. With the increase in Hajj and Umrah travel make the competition between travel even tighter. Marketing strategy is one of the most important things in how to sell a product to the public large. Marketing can be done in two ways, namely conventional and digital marketing. PT. Alamin Ahsan Travel carries out various marketing strategies, such as providing information about the products they own, and by growing pilgrims' confidence in travel which is also important in marketing strategy. By using various methods, strategies marketing will be able to complement each other and travel can continue compete with other Umrah and Hajj travel agencies. This study used descriptive qualitative method. The results of the research that marketing at PT Alamin is already using digital. This research can adapt to applied studies in the field of tourism marketing.